Experimental Study On The Performance Of Small Solar Updraft Tower In The Climate Region - Saadun, Mohd Noor Asril; Sidik, N.A.C. (Penerbit Universiti Malaysia Pahang, 2020)
Solar updraft tower (SUT) power plant is a unique system using solar energy, which consists of three main parts: the chimney, turbine, and collector. In tropical climate conditions, especially in Malaysia, the application of solar chimney can be deemed more competitive compared to other renewable energy systems. In this study, one prototype with a dimension of 3.5 m in diameter for the collector and 5 m height for the chimney, was built in Melaka, Malaysia. Vital parameters such as temperature field, pressure, humidity, and air movement were measured using data logger and stored using non-volatile memory. The most exciting finding was that the temperature and pressure difference was significantly seen during the experiment along the day. There was a significant surge for the humidity in the morning with an average of above 95% and the ambient temperature was approximately 35 °C due to low solar radiation. The humidity kept decreasing after sunrise due to the greenhouse effect produced in the solar collector. With the collection of these critical parameters, a solar chimney power plant was adequate to function and generate power from solar radiation in a country such as Malaysia, which is based in the equatorial region. These studies are limited as the analysis focused mainly for high radiation and did not investigate efficiency during low solar radiation. The addition of heat storage underneath the collector with current techniques is another direction of research for continuous system operation, particularly during low solar radiation. It is proposed that the synthesis of these factors should be extensively explored in future studies coupled with the application of heat storage.